THE MINIMIZATION OF NA AGRICULTURAL PRODUCT COST FUNCTION IN FERTILIZER EXPERIMENTS - Carranza, CristiÃ¡n; Gomes, F. Pimentel (REVISTA DE AGRICULTURA, 2015)
THE MINIMIZATION OF NA AGRICULTURAL PRODUCT COST FUNCTION IN FERTILIZER EXPERIMENTS